Assessing the Adoption and Diffusion of Natural Resource Management Practices: Synthesis of a New Set of Empirical Studies - Stevenson, James R.; Vlek, P. (CGIAR Independent Science and Partnership Council, 2018)
This synthesis study provides the context and rationale for a set of new empirical studies estimating the adoption of natural resource management (NRM) practices that could have both private economic benefits and public environmental benefits following adoption. The nine case-studies covered here were commissioned by the CGIAR Standing Panel on Impact Assessment (SPIA) (https://cas.cgiar.org/spia) in 2016, and focus on practices that have been part of the CGIAR research agenda over the past decades and have been the subject of multiple claims in CGIAR annual reports regarding widespread farmer adoption of these innovations. They are: conservation agriculture; alternate wetting and drying; fertilizer micro-dosing; integrated soil fertility management; and agroforestry.